1985
DOI: 10.1172/jci111705
|View full text |Cite
|
Sign up to set email alerts
|

Functionally thrombasthenic state in normal platelets following the administration of ticlopidine.

Abstract: To elucidate the bleeding tendency that follows the administration of ticlopidine, we investigated the skin bleeding time and some ex vivo functions of platelets obtained from eight healthy volunteers before and 1 wk after daily administration of 500 mg of ticlopidine. We found the following: ticlopidine significantly (P < 0.001) prolonged the skin bleeding time and impaired the binding of radiolabeled fibrinogen and von Willebrand Factor, the clot retraction and the aggregation of platelets in response to ADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(94 citation statements)
references
References 55 publications
7
87
0
Order By: Relevance
“…prevented by ticlopidine. Ticlopidine is a well-known anti platelet agent that inhibits platelet aggregation induced by various stimulators (23). In the present study, reduc tion of platelet count in the control group was observed, and ticlopidine inhibited the thrombus formation and tended to prevent the reduction of circulating platelets.…”
Section: Effects On Extracorporeal Circulationsupporting
confidence: 60%
“…prevented by ticlopidine. Ticlopidine is a well-known anti platelet agent that inhibits platelet aggregation induced by various stimulators (23). In the present study, reduc tion of platelet count in the control group was observed, and ticlopidine inhibited the thrombus formation and tended to prevent the reduction of circulating platelets.…”
Section: Effects On Extracorporeal Circulationsupporting
confidence: 60%
“…This antagonism is non-competitive, irreversible, and results in 50-70% inhibition of platelet fibrinogen binding. Clopidogrel has also been reported to prevent thrombocyte aggregation by inhibiting fibrinogen binding to activated fibrinogen receptors (GPllbllla complex) on the platelets (Dunn et al 1984;Di Minno et al 1985). Inhibition of platelet aggregation occurs 24-48 h following the oral intake of clopidogrel and reaches its maximum level in 3 to 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…26 The mechanism by which ticlopidine inhibits platelet aggregation is completely different from the mechanism of aspirin because it does not have any effects on cyclooxygenase.27 Recent studies indicate that ticlopidine inhibits ADP-mediated platelet aggregation15 and antagonizes the interaction of fibrogen with its platelet receptor, the membrane glycoprotein IIb-IIIa. 16 Ticlopidine has been given to patients with several clinical forms of atherosclerosis, such as transient ischemic attack, stroke, and peripheral vascular disease. In patients who have had stroke, ticlopidine decreased the incidence of such later vascular accidents as stroke, myocardial infarction, and vascular death by 23.3%.28 Ticlopidine was also effective in patients with peripheral vascular disease in a randomized, double-blind placebo-controlled study with a duration of 21 months.…”
Section: Ticlopidine: Mode Ofaction and Clinical Usementioning
confidence: 99%
“…Ticlopidine, unlike aspirin, does not block cyclooxygenase but appears to interfere with the ADP-mediated platelet activation mechanism15 and the platelet fibrinogen receptor. 16 The control group was not treated with aspirin because acetylsalicylic acid was not widely used for treatment of unstable angina in Italy in 1986, when the protocol was designed. Nowadays, aspirin is more widely used.…”
mentioning
confidence: 99%